2006
DOI: 10.1002/cncr.21861
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Wilms tumor gene (WT1) mRNA expression in soft tissue sarcoma

Abstract: This paper focuses on the voltages electromagnetically induced by the multiple return strokes involved in a triggered lightning on an overhead power line and a vertical signal line of an automatic weather station (AWS), and the backflow currents and residual voltages in a surge protection device (SPD) embedded in the power line. Pulses of voltage on the overhead power line corresponding to the return strokes with the peak currents ranging from −6.67 to −26.47 kA showed bipolar features. Subpeaks and main peaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Moreover, several reports indicating an oncogenic, rather than a tumor-supressor, role of the wild-type WT1 gene have been accumulated. For example, high expression levels of WT1 messenger ribonucleic acid (mRNA) are correlated with poor prognosis in leukemias [15], breast cancer [19], and soft tissue sarcomas [33]. Treatment with WT1 antisense oligomers specifically causes growth inhibition in leukemic blast cells [2,39] and in cell lines derived from cancers of the lung, stomach, colon, and breast [24,41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several reports indicating an oncogenic, rather than a tumor-supressor, role of the wild-type WT1 gene have been accumulated. For example, high expression levels of WT1 messenger ribonucleic acid (mRNA) are correlated with poor prognosis in leukemias [15], breast cancer [19], and soft tissue sarcomas [33]. Treatment with WT1 antisense oligomers specifically causes growth inhibition in leukemic blast cells [2,39] and in cell lines derived from cancers of the lung, stomach, colon, and breast [24,41].…”
Section: Introductionmentioning
confidence: 99%
“…Although the WT1 gene was primarily considered to be a tumor-suppressor gene, recent studies have demonstrated an overexpression of the wild-type WT1 gene in leukemias [15] and various solid neoplasms such as those of the breast [16,19], lung, digestive tract [25,26], pancreas [23], bone, and soft tissues [33,37]. Moreover, several reports indicating an oncogenic, rather than a tumor-supressor, role of the wild-type WT1 gene have been accumulated.…”
Section: Introductionmentioning
confidence: 99%
“…These factors may reduce the mRNA levels of the tumor specimens, which may disturb the accurate analysis between mRNA levels and clinical data. Sotobori et al [17] investigated WT1 mRNA expression in adult cases of soft tissue sarcoma. They observed the WT1 mRNA expression levels in soft tissue sarcomas to be significantly greater than the levels in normal soft tissues, and the disease-specific survival rate for patients with high WT1 mRNA expression levels was found to be significantly poorer in comparison with the rate for patients with low WT1 mRNA expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…High WT1 mRNA expression levels have been correlated with a biologically aggressive phenotype that has been associated with a poor prognosis for leukemia (21) and sarcoma (22). Leukemia patients who had high levels of WT1 mRNA had increased drug resistance and worse overall survival than patients who had low levels of WT1 mRNA (21,23).…”
Section: Introductionmentioning
confidence: 99%